Fraud risk assessment and detection of Fraud: The moderating effect of personality. - Jaffar, Nahariah; Haron, Hasnah; Mohd Iskandar, Takiah; Salleh, Arfah (Canadian Center of Science and Education, 2011)
External auditors are required by the auditing standards to provide reasonable assurance that the financial statements are free from material misstatements. Inability of the external auditors to detect material misstatements, particularly fraud, may expose the external auditors to litigation. The present study aims to examine the moderating effect of personality factors (that are neuroticism, extraversion, conscientiousness, openness to experience and agreeableness) on the relationship between the external auditors’ ability to assess fraud risk and their ability to detect the likelihood of fraud. The present study utilizes an experimental approach by sending case materials to audit partners or audit managers attached to auditing firms operating in Malaysia. The result, however, shows that none of the personality factors has moderating effect on the relationship between the external auditors’ ability to assess fraud risk and their ability to detect the likelihood of fraud.